Analysis of the formation mechanism and occurrence possibility of Post-Stenotic Dilatation of the aorta by CFD approach. (October 2020) - Zhang, Xuelan; Luo, Mingyao; Fang, Kun; Li, Jiehua; Peng, Yuan; Zheng, Liancun; Shu, Chang
Highlights: Three dimensional non Newtonian (Carreau Yasuda model) hemodynamic simulations are performed. A novel hemodynamic parameter is proposed to evaluate the intensity of the aortic vortical structures. Pathogenesis behind Post Stenotic Dilatation (PSD) formation and the type of coarctation that easily triggers PSD are analyzed. Formation of PSD is due to the vortical structures with relatively high swirling strength. Risk of PSD formation (even aneurismal dilation) enhances with an increase of coarctation degree. Graphical abstract: Abstract: Background and objective : Post-Stenotic Dilatation (PSD), the common complication of coarctation of the aorta (COA), is a progressive disease involving aortic aneurysm and even rupture. However, there has been no definitive method that could investigate the mechanism of PSD formation, progression and rupture. The purpose of the present work is to analyze the mechanism behind PSD formation and to further assess the risk of COA patients with different coarctation degrees deteriorating into PSD. Method : Three-dimensional non-Newtonian (Carreau-Yasuda) hemodynamic simulations are performed throughout the cardiac cycle, and a novel parameter ( λ c i ¯ intensity) is proposed to evaluate the intensity of vortices within the aorta. The PSD geometry is reconstructed from Computed Tomography scans. To analyze the formation mechanism and occurrence possibility of PSD, the computer technology is utilized to restore the expansive and/or narrow regions to obtain its previous state (COA) and control group (Normal), and to modify the minimum diameter to obtain the aortas with different coarctation degrees. The clinical cases of pre- and post-operation are further introduced to verify the analysis. Results : Compared with the Normal, the vortical structures with higher swirling strength are generated and accumulated at the downstream of the coarctation segment after COA occurrence, and partially disappear in the wake of PSD formation. The sequence of λ c i ¯ intensity is COA > PSD > Normal and pre-operation > post-operation. With increasing the degree of coarctation, the λ c i ¯ intensity is higher and the jet-flow becomes more drastic. Conclusions : The formation of PSD is caused by the vortical structures with higher swirling strength accumulating at the downstream of the coarctation segment. An increase in coarctation degree elevates the risk of PSD occurrence and even aneurysmal dilatation.